Label-free proteomic analysis reveals the hepatoprotective mechanism of gypenosides in liver injury rats - Chen, Yu; Ma, Lizhou; Wang, Yibo; Zhang, Jiarui; Pei, Tianhe; Wang, Miao (Frontiers in Pharmacology, 2024)
Gypenosides (GPs), derived from the traditional Chinese medicine Gynostemma pentaphyllum (Thunb.) Makino, exhibit hepatoprotective properties, yet their precise therapeutic mechanism remains elusive. This study aimed to elucidate the hepatoprotective mechanism of GPs and identify potential therapeutic targets for chronic liver disease by comparing proteomic profiles of normal rats, those with carbon tetrachloride (CCl4)-induced liver injury, and GPs-treated rats. Utilizing label-free proteomics, we identified 2104 differentially expressed proteins (DEPs) associated with liver injury and 1974 DEPs linked to the hepatoprotective effects of GPs. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that GPs primarily restored metabolic processes involving valine, leucine, and isoleucine degradation, as well as propanoate and butanoate metabolism, and steroid hormone biosynthesis during liver injury. Subsequently, overlapping the two groups of DEPs identified 1508 proteins reversed following GPs treatment, with key targets further validated by parallel reaction monitoring (PRM). Eight target proteins were identified for GPs treatment of liver injury, including Lgals3, Psat1, Phgdh, Cyp3a9, Cyp2c11, Cyp4a2, Glul, and Ces1d. These proteins not only represent targets of action for GPs but may also serve as potential therapeutic targets, elucidating the pathophysiology of chronic liver disease.